Judicial education: A documentary review from the socioformation - Medina-Peñaloza, Sergio Javier (2020)
The purpose of this article is to expose the need for professional justice to be delivered by judges, through socioformation in judicial education. A general documentary analysis was carried out from a socio-formative approach, based on judicial education that resulted in the shortage of vocation in the judicial service, manifested in the increasingly intense social demand for justice. The achievement of a justice that profoundly and positively impacts the social life and the perception of the reality of the citizens implies: that judicial education be given its place as the fundamental guiding axis of judicial policy, the backbone of the development of Power. Judicial; and that education is developed in the margin of socioformation as a basis for the design of vocational measurement parameters.